Autenticidade molecular de produtos cárneos - Felkl, Gabriela Sartori (2014)
Proper authenticity of a meat product as your identity standard (labeling) is essential by economic issues, health and religious as well as being a requirement in existing organs of food. However, the identification of constituents in a meat product is still a considerable challenge for the authorities, as it is not always possible to detect them by conventional methods, especially after processing the product. This limiting factor makes the fraud by replacement of one animal species by another of lower economic value a very common act. This study aims to determine the presence of pork and chicken in processed products from the molecular diagnostic by Polymerase Chain Reaction (PCR). For this, we carried out the molecular diagnosis of swine and chicken species, first extracting the target DNA, followed by amplification of the same. Thus, the primers of chicken and pork species were evaluated for specificity and sensitivity, showing effective, with a detection limit from 0.1%. By analyzing 27 samples of commercial meat products, the PCR method has proved satisfactory and robust, once adulteration as been detected in three samples. Besides not demonstrate variation us results regarding to heat treatment used in the product.